Private law framework for blockchain - Kiskis, Mindaugas (Frontiers in Blockchain, 2024)
Current attempts to regulate blockchain technology are mainly based on securities law framework, which considers crypto tokens and digital assets as either securities, currencies or derivatives thereof. The main limitation of such approach lies in its inability to accommodate the diverse legal rights, obligations and assets that blockchain technology can virtually reproduce. Already in 2017–2018 there were attempts to tokenize rights outside of securities law framework, these initiatives served more as makeshift solutions to circumvent securities regulations than as thorough frameworks for managing real-world assets and commercial activities. This article conducts a comparative and historical analysis of blockchain regulatory initiatives in Europe and the US, positing that the regulation of blockchain technology through a securities law lens is driven by reactionary opportunism. Such a basis is deemed inappropriate and insufficient, as securities laws being a field of public law were not designed to govern real-world assets and commerce, which fundamentally rely on the principles of laissez-faire and freedom of contract inherent in private law. A regulatory stance focused solely on public law overlooks the full potential of blockchain technology, and risks stifling innovation and practical applications. To illustrate this, the article presents case study of tokenization of contractual rights demonstrating that securities law-focused legal regulations, such as the EU Regulation 2023/1114 on Markets in Crypto-Assets (MiCA) and Regulation 2022/858 on Distributed Ledger Technology (DLT), inadequately address the field of private commerce. Based on the analysis, the article concludes that comprehensive legal framework for blockchain technology shall combine public and private law regime akin to the regulation of traditional rights, obligations and assets.